2018
DOI: 10.1016/j.chb.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigating gender and spatial measurements in instructional animation research

Abstract: Instructional animation research has been extensive but the results are inconsistent. Amongst a number of possible factors to explain these inconclusive results (e.g., the negative influence of transient information), the influence of spatial ability and gender are less explored. This paper reports three experiments that compared the effectiveness of learning a handmanipulative task (Lego construction) under various conditions with direct examination of the relationship between gender, spatial ability and inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 101 publications
(112 reference statements)
0
17
0
Order By: Relevance
“…Several studies have indicated that, generally speaking, men have better spatial awareness than women as a result of different factors. This statement has even been reaffirmed in conclusions drawn from more recent research [34][35][36][37].…”
Section: Discussionmentioning
confidence: 68%
“…Several studies have indicated that, generally speaking, men have better spatial awareness than women as a result of different factors. This statement has even been reaffirmed in conclusions drawn from more recent research [34][35][36][37].…”
Section: Discussionmentioning
confidence: 68%
“…Finally, and most importantly, because of their temporal impairment, deaf learners find the mental simulation and sequencing of the evolution of dynamic situations via static pictures more difficult than learners with normal hearing (Conway et al, 2009). Dynamic visualization presentation could, however, act as a compensating support, as previous studies have shown for learners with low visuospatial abilities (Berney & Bétrancourt, 2016;Boucheix & Schneider, 2009;Hegarty, 2004;Hegarty, Kriz, & Cate, 2003;Höffler & Leutner, 2011;Wong, Castro-Alonso, Ayres, & Paas, 2018). F I G U R E 2 Examples of two overtaking situations, when the distance from the vehicle in front (on approach) is short (a) and when the distance from the vehicle is longer (b).…”
Section: Time Sequencing Issues In Deaf Peoplementioning
confidence: 95%
“…Results showed fewer errors in the animated format than in the sequential-static format for deaf people only. Animation may act as a compensatory factor (Boucheix & Schneider, 2009;Höffler & Leutner, 2011;Wong et al, 2018). However, much more research is needed to address this issue and confirm (or disprove) this result.…”
Section: Animation As a "Temporal Compensation" Processing For Deafmentioning
confidence: 99%
“…One limitation of this review is that we considered the cognitive load theory evidence for groups of students, without consideration of their individual characteristics (besides expertise levels). Future directions for instructor- and learner-managed solutions could not only consider learners’ expertise as an important individual characteristic, but also assess the moderating effects of other learners’ properties, such as gender (e.g., Castro-Alonso et al, 2019b ; Heo & Toomey, 2020 ; Wong et al, 2018 ), visuospatial processing (see Allen et al, 2019 ; Buckley et al, 2018 ; Castro-Alonso, 2019 ), mental effort (e.g., van Gog et al, 2020 ), and motivation (e.g., Eitel, Endres, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%